2019
DOI: 10.1371/journal.pmed.1002941
|View full text |Cite
|
Sign up to set email alerts
|

Trends in prescription opioid use and dose trajectories before opioid use disorder or overdose in US adults from 2006 to 2016: A cross-sectional study

Abstract: BackgroundWith governments’ increasing efforts to curb opioid prescription use and limit dose below the Centers for Disease Control and Prevention (CDC)-recommended threshold of 90 morphine milligram equivalents per day, little is known about prescription opioid patterns preceding opioid use disorder (OUD) or overdose. This study aimed to determine prescribed opioid fills and dose trajectories in the year before an incident OUD or overdose diagnosis using a 2005–2016 commercial healthcare database.Methods and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…Across the 4 identified groups, we observed a low dose range (mean daily dose between 0 to 20 daily MME) of prescribed opioids and less than 5% of older patients, the majority of whom were among the cases, receiving doses at or above the dose threshold of 90 daily MME. Compared to evidence observed in younger adults with ORAE [ 25 ], a lower dose range (0 to 20 daily MME versus 3 to 150 daily MME) and a lower proportion with ≥90 daily MME (2.4% versus 28.8%) was observed among older adults with a similar diagnosis of ORAE, suggesting that there is a unique opioid dosage pattern preceding the incident ORAE encounter in the older population.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Across the 4 identified groups, we observed a low dose range (mean daily dose between 0 to 20 daily MME) of prescribed opioids and less than 5% of older patients, the majority of whom were among the cases, receiving doses at or above the dose threshold of 90 daily MME. Compared to evidence observed in younger adults with ORAE [ 25 ], a lower dose range (0 to 20 daily MME versus 3 to 150 daily MME) and a lower proportion with ≥90 daily MME (2.4% versus 28.8%) was observed among older adults with a similar diagnosis of ORAE, suggesting that there is a unique opioid dosage pattern preceding the incident ORAE encounter in the older population.…”
Section: Discussionmentioning
confidence: 56%
“…The adverse effects of opioids defined by the E codes include any severe reactions to illicit opioids (i.e., heroin) or correct use of prescribed opioids (i.e., methadone, opioid antagonists, and other opioids) that lead to an emergency department or hospital visit. Consistent with prior studies [ 4 , 25 ], when identifying patients with incident ORAE encounter, we excluded ICD-10-CM codes that indicated “in remission” or “subsequent encounter.” The date of the first ORAE encounter represented the “index” date.…”
Section: Methodsmentioning
confidence: 99%
“…Analyzing 2005–2016 claims data, Yu-Jung Wei and colleagues [21] identified more than 200,000 adults with new claims related to opioid use disorder or overdose. They found that, by the end of the study period, nearly one-half had filled no opioid prescriptions in the 12 months prior to an incident opioid use disorder diagnosis or overdose.…”
Section: Determinants Of Opioid Use–related Harmsmentioning
confidence: 99%
“…Group‐based trajectory modelling (GBTM) is a semi‐parametric latent class approach to identify subgroups sharing similar patterns, that is, trajectories, in longitudinal data such as drug dose 4–6 . GBTM assumes that individual trajectories within class are homogeneous, which confers attractive computational properties over alternative latent class approaches 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, guidelines for the conducting of and reporting 7 on trajectory studies have been proposed to limit model misspecification 7 . Although GBTM have been routinely used to identify patterns of drug adherence, few studies 6,8,9 were focused on patterns of medication dose. For example, Wei et al identified five distinct patterns of opioid morphine dose prescribed during the year before an opioid use disorder or overdose, including low and escalating dose 6 …”
Section: Introductionmentioning
confidence: 99%